130: PATTERN OF LYMPH NODE METASTASES IN GASTRIC CANCER—A SIDE-STUDY OF THE MULTICENTER LOGICA-TRIAL. (23rd April 2022) - De Jongh, C; Triemstra, L; Van Der Veen, A; Brosens, L; Luyer, M; Stoot, J; Ruurda, J; Van Hillegersberg, R
Abstract: Background and aim: The relation between tumor characteristics and the pattern of lymph node (LN) metastases in gastric cancer is unclear, especially following neoadjuvant chemotherapy (NAC). Therefore, the aim of this study is to analyze the pattern of LN metastases of gastric cancer. Methods: Individual LN stations were separately collected (no. 7–9, 11 and 12a) or clearly marked at the resection specimen (no. 1–6), and were analyzed for all patients included in the LOGICA-trial. The LOGICA-trial was a multicenter randomized trial comparing laparoscopic versus open gastrectomy in ten hospitals. Total and distal D2-gastrectomy were performed for resectable gastric cancer (cT1–4aN0–3bM0). The pattern of metastases per LN station was related to tumor location, cT-stage, Lauren classification and NAC-treatment. In addition, the distribution of LN metastases over the individual LN stations was assessed for four subgroups based on tumor location, cT-stage, Lauren classification and NAC-treatment, and several combinations of these characteristics. Results: Between 2015–2018, 212 patients underwent D2-gastrectomy, of whom 158 (75%) received NAC. LN metastases were present in 121 patients (57%). Proximal tumors metastasized predominantly to proximal LN stations (no. 1, 2, 7 and 9; OR > 1, P < 0, 05), and distal tumors to distal LN stations (no. 5, 6 and 8; OR > 1, P > 0, 05). However, distal tumors still metastasized to proximal LN stations, and vice versa. Each individual LN station (no. 1–9, 11 and 12a) showed metastases, regardless of the tumor location, cT-stage, histological subtype and NAC-treatment, including station 12a for cT1N0-tumors. Although LN metastases were present more frequently in cT3–4- versus cT1–2-stage (59% versus 51%; P = 0, 259) and in diffuse versus intestinal tumors (66% versus 52%; P = 0, 048), the pattern of LN metastases was similar for these subgroups. A sensitivity analysis was performed with only the NAC-treated patients to test the robustness of these results, which showed a similar pattern of LN metastases after NAC. Conclusion: Although the pattern of LN metastases is related to tumor location in gastric cancer, metastatic spread occurred in all LN stations (no. 1–9, 11 and 12a), regardless of the tumor location, cT-stage (including cT1N0-tumors), histological subtype and NAC-treatment. Therefore, all LN stations (including 12a; D2-lymphadenectomy) should be routinely dissected during gastrectomy.